(untitled) (Foro de Educacion, 2015)
This article presents an analysis of the change of meanings teachers and publishers attribute to textbooks in the context of recent history. These are the results of an investigation which brings the small set of studies related to the use of textbooks trying to open a connection between the art of teaching and the publishing production which enrolled in a stage of transformations of culture printed. In particular, it focuses on the meaning associated with the use of fourth, fifth and sixth grade textbooks from primary school in Buenos Aires, Argentina. The methodological strategy involved the six focus groups of teachers, twelve observations gathered in class, only as an observer; observation texts, notebooks and folders of six courses and twenty thorough interviews to teachers and publishers. The study results showed that the selection and use of textbooks that teachers perform are associated with readings in the educational context: the classroom, the children, the link with the knowledge, relationships with families. The interpretation that publishers make about these meanings and practices give rise to a set of meanings involved in the design and layout of the books, in turn, try to combine with business objectives. In order to provide answers to requirements of everyday practice, teachers hold a huge variety of joints, omissions and additions not included in the source production editors checking the productive nature of teaching practices.